THE INFLUENCE OF TIKTOK CONTENT MARKETING, LIVE COMMERCE, AND USER-GENERATED CONTENT (UGC) ON PURCHASE INTENTION - Raisya Safitri Puteri Fadjriatni (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2026)
PURPOSE - This study aims to analyze the influence of TikTok content marketing, live commerce, and user-generated content (UGC) on consumers' purchase intentions for Grace & Glow skincare products in Yogyakarta. The background of this study is the increasing use of TikTok as an effective digital marketing platform for fostering consumer engagement and purchase intent, especially among younger generations.METHODOLOGY - This study used a quantitative, explanatory-causal design. A sample of 187 respondents was obtained through purposive sampling, with the criteria of TikTok users aged 17 or older who had watched Grace & Glow promotions. Data were gathered through a five-point Likert-scale questionnaire and analyzed using multiple linear regression in IBM SPSS 27.FINDING - The results of the study indicate that the three independent variables significantly and positively influence purchase intention. Live streaming activities on TikTok increase direct engagement and customer trust, while marketing content and UGC enhance positive brand perception. Theoretically, this study expands the understanding of social interaction-based digital marketing strategies. In practice, these findings offer recommendations for local brands to optimize interactive communication strategies to increase consumer purchase intention in the era of social media-based marketing.